Social and health behaviors in youth of the streets of Ibadan, Nigeria (2006)
Objectives: This study documents the extent and impact of perceived patterns of behavior in a sample of youths of the streets of Ibadan, Nigeria, with the purpose of implementing a Life Skills Educational (LSE) intervention. Method: The study uses both qualitative and quantitative methods of data collection. Qualitatively, two Focus Group Discussions (FGD) and two in-depth interviews (IDI) with 20 boys and 2 community leaders were conducted on separate occasions for the purpose of eliciting commonly exhibited behaviors and patterns of street youth. Quantitatively, 169 youths (89.3% male) were consecutively interviewed from five subcultural areas in Ibadan, Nigeria. Street youths were accessed through a snowballing technique made possible by “Area boys” (AB, adults, who serve as a symbol of authority for street children). Results: The mean age of participants was 18.4 years. The majority was on the street for financial reasons, had been on the street for more than 1 year, and had not completed their primary schooling. While youths of the street were economically viable, 69% had a history of alcohol abuse, 14% of drug abuse, and 24% operated as drug couriers; 46% reported school refusal, 27% school suspension, and 47% school truancy. Forty-nine percent admitted to being sex workers and 11% had been raped and were, therefore, at risk of contacting sexually transmitted diseases (STD). One-third of youths had been arrested for various offenses, including street fighting and drug use. While females were in the minority, they were more likely to engage in antisocial behaviors compared with boys. Conclusions: Although many youths of the street display antisocial behaviors, they also are an economically viable group. Some of their antisocial behaviors may have been exhibited within the context of economic survival.